On the importance of a procedurally fair organizational climate for openness to change in law enforcement - Bradford, Ben (2020)
Objectives Drawing on recent work in policing and organizational psychology, we examined factors related to openness to organizational change and to adopting evidence-based interview techniques among law enforcement investigators. Hypotheses We hypothesized that a procedurally fair organizational climate would predict outcomes tied to organizational change, mediated by organizational identification and perceived legitimacy. We also predicted that procedural justice factors would be stronger predictors than outcome-oriented factors (i.e., rewards and sanctions). Methods Study 1 surveyed law enforcement investigators (N = 711) about their attitudes towards and behaviors within their organization (i.e., perceived procedural fairness of one’s organization, identification, legitimacy, compliance, empowerment, and extra-role behavior). Study 2 conceptually extended this survey to interviewers (N = 71) trained in a new, evidence-based interviewing approach adding likelihood of future use of the novel interviewing approach as an outcome. Results In Study 1, the more investigators thought their organization had a procedurally fair climate, the more they identified with the organization and perceived it as legitimate. Framing compliance, empowerment and extra-role behavior as associated with openness to change, we found that legitimacy predicted compliance and tendency toward extra-role behavior (i.e., going “above and beyond”), while level of identification predicted feelings of empowerment and extra-role behavior. Study 2, partially replicated findings from Study 1, and found that motivation to attend the training also predicted likelihood of future use. Conclusions These studies highlight the value of a procedurally just organizational climate framework in understanding law enforcement interrogators’ propensity towards implementing new evidence-based interrogation techniques